Women empowerment in Namibia: Measurement, determinants and geographical disparities. (September 2020) - Kazembe, Lawrence N.
Highlights: This study provides a first exposition of women empowerment in Namibia. Developed five specific and overall measures of women empowerment in Namibia. Empowerment associated with residence, education, access to news and TV watching. Varied geographical disparities were observed with overall women empowerment. Underlying cultural or ethnic processes has spatial effect on women empowerment. Abstract: There is growing recognition that removal of gender inequality and women empowerment are central to realizing development goals. Attainment of gender equality would further promote economic growth, reduce poverty, improve maternal and child health in related sustainable development goals. The Demographic and Health Survey (DHS) data provide an opportunity to study women empowerment in Namibia, while examining possible determinants and geographical disparities. We developed five separate indices: self-esteem, decision making, contraception use, sexual relations and occupation and earnings index using scoring and factor analysis. We then constructed an overall empowerment index and fitted an ordinal hierarchical regression model to estimated the effects of demographic, socio-economic, exposure to media and geographical factors on empowerment outcome. Findings indicate that women empowerment was associated with place of residence, education level, access to newspaper and frequent watching of TV. This study provides a first exposition of women empowerment in Namibia and helps clarify socio-demographic and economic variables important to explaining empowerment. More central in this study is the extension to include spatial random effects to capture the influence of unobserved or unmeasured geographical factors, which are key to permit modelling of underlying cultural or ethnic processes that influence women empowerment in Namibia.